Lab-on-chip for magnetic resonance relaxometry detection for rapid malaria diagnosis - Kong, Tian Fook (2015)
Malaria is an infectious disease that affects 3.4 billion people, especially in the tropical and subtropical countries such as Africa and South-East Asia. The major challenges in current clinical malaria diagnostics are in obtaining a sensitive, robust, fast, and inexpensive measurement from patient blood sample. While one of the leading causes of the high mortality rate in malaria cases is the delay in medical diagnosis and treatment. Prompt diagnosis and timely treatment for malaria is often difficult to come by in malaria endemic area. Most malaria deaths can be prevented if diagnosis and effective treatment were administered within 24 hour after the onset of the first symptom. Therefore, access to fast, sensitive and reliable diagnostic tool is of inevitable importance. Rapid diagnostic tests (RDTs) such as the dipsticks and quantitative buffy coat were developed to aid the detection of malaria. However, negative RDTs results cannot be accepted directly without confirmation by microscopic examination. At present, Giemsa-stained microscopic examination of thick blood smear remains the gold standard for laboratory diagnosis of malaria. Although the procedure is labor intensive, time consuming and requires a well-trained and highly experienced personnel, Giemsa microscopic examination is still being practiced in the current clinical setting for more than a century.